2013
DOI: 10.1210/jc.2013-1279
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characteristics and Clinical Diagnosis of Maturity Onset Diabetes of the Young Due to Mutations in HNF1A, HNF4A, and Glucokinase: Results From the SEARCH for Diabetes in Youth

Abstract: In this systematic study of MODY in a large pediatric US diabetes cohort, unselected by referral pattern or family history, MODY was usually misdiagnosed and incorrectly treated with insulin. Although many type 2 diabetes-like metabolic features were less common in the mutation-positive group, no single characteristic identified all patients with mutations. Clinicians should be alert to the possibility of MODY diagnosis, particularly in antibody-negative youth with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
276
2
29

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(319 citation statements)
references
References 32 publications
12
276
2
29
Order By: Relevance
“…Our main finding that at least up to 6.5% of antibody-negative children with diabetes have MODY is somewhat lower than the proportion reported in other studies [11][12][13][14]. Still, our data might be more robust.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Our main finding that at least up to 6.5% of antibody-negative children with diabetes have MODY is somewhat lower than the proportion reported in other studies [11][12][13][14]. Still, our data might be more robust.…”
Section: Discussioncontrasting
confidence: 75%
“…Although we and others have estimated the prevalence of monogenic diabetes to be 1.1-4.2% of all children with diabetes [11][12][13][14], no study has yet screened a nationwide population-based cohort in a systematic way.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, screening approaches are essential to gain estimates of the true prevalence and to identify misdiagnosed MODY patients to ensure they benefit from optimal treatment. To date, several studies have screened whole paediatric clinic populations and have estimated MODY to represent between 1.1% and 4.2% of all children with diabetes [7][8][9][10]. The SEARCH for Diabetes in Youth study has been the largest to date [9], using a systematic approach, sequencing genomic DNA from 586 children who were negative for islet autoantibodies and had a fasting C-peptide >0.8 ng/ml.…”
Section: Recognising Mody Is Difficultmentioning
confidence: 99%
“…To date, several studies have screened whole paediatric clinic populations and have estimated MODY to represent between 1.1% and 4.2% of all children with diabetes [7][8][9][10]. The SEARCH for Diabetes in Youth study has been the largest to date [9], using a systematic approach, sequencing genomic DNA from 586 children who were negative for islet autoantibodies and had a fasting C-peptide >0.8 ng/ml. In this study, mutations for the three main MODY genes (HNF1A, HNF4A or GCK) were identified in 8% of the cohort, suggesting an overall population prevalence of 1.2%.…”
Section: Recognising Mody Is Difficultmentioning
confidence: 99%
See 1 more Smart Citation